COMPARATIVE STUDY OF KATO'S THICK-SMEAR TECHNIQUE WITH CONCENTRATION FORMALIN-ETHER AND FLOTATION METHODS FOR QUANTITATIVE AND QUALITATIVE DIAGNOSIS OF INTESTINAL HELMINTH INFECTIONS - J.Massoud; F.Arfaa; H.Jalali; M.Reza (Tehran University of Medical Sciences, 1978)
This investigation was performed on 1056 stool samples collected from Isfahan area (with high intensity of infection) and Dasht-Mishan area of Khuzestan. As indicated in Tables 1, 2 and 3 the results of Kato thick-smear technique is comparable to those conventional methods of Formalin-ether and Flotation methods, plus low cost, simplicity and practicability of Kato's thick-smear. For Ascaris eggs the Kato method is ideal for epidemiological studies: For Hookworm and Trichostrongylus infections, Kato method was less sensitive but still it was at an acceptable level for epidemiological surveys. Also, Kato technique was more sensitive in areas where the intensity of infection is high. The conclusion is that the Kato Thick-Smear technique is cheap, fast, convenient and ideal for mass-diagnosis in epidemiological surveys of intestinal helminthiasis.